Demand for secondary schooling in Pakistan: A cross income group analysis - Ali, Kazim (Asian Journal of Contemporary Education, 2024)
Secondary education for all is one of the UN’s attainable goals. Many countries, including Pakistan, are struggling to achieve this target. Earlier research has attempted to analyze the determinants of secondary schooling by taking the total income of households. However, households of different income groups respond differently to varying socio-economic factors. This study attempts to identify the household-level socio-economic determinants of secondary schooling across different income groups in Pakistan. It utilizes national survey data from the Pakistan Social and Living Standards Measurement (PSLM) Survey 2019-20. We selected households from the dataset that had at least one member of secondary school age (13-20 years). Households that enrolled a secondary school-age member in school or whose member achieved secondary schooling were categorized as having demand for secondary schooling. Furthermore, instead of taking the total income of households, study takes six categories of income. The results of logit estimation show that demand for secondary schooling increases across successive income groups, indicating secondary schooling is a normal commodity. The proportion of male school-going age members and having a female head increase the likelihood of demand for secondary schooling. The study recommends that policies to increase enrollment at the secondary level may focus more on lower-income groups and on the education of females.